The Impact of Intellectual Capital On The Soundness Of Islamic Banks In Indonesia (Journal of Business and Management, 2022)
Abstract. Knowledge-based business is needed to gain and maintain a firm's competitive advantage by enhancing its innovation, information, and human knowledge, thereby creating value-added for the firm. This study examines the three components of Intellectual Capital, namely Capital Employed Efficiency (VACA), Human Capital Efficiency (VAHU), and Structural Capital Efficiency (STVA), and whether they impact the soundness of Islamic banking as measured by the RGEC (risk profile, good corporate governance, earnings, and capital) rating method. The RGEC rating method was measured by composite rating from NPF, FDR, GCG, ROA, ROE, OEOI, and CAR The data were obtained from 11 Islamic banks registered with the OJK for six periods from 2015 – 2020 with 66 banking annual financial reports. This study uses panel data regression analysis with the Fixed Effect Model (FEM) using STATA 17.0 software. The results of this study indicate that STVA has a negative impact on the soundness of Islamic banks in Indonesia. Meanwhile, VACA and VAHU do not impact the soundness of Islamic banks in Indonesia.Keywords: Intellectual Capital, VACA, VAHU, STVA, RGEC